2019
DOI: 10.1039/c8cp06471g
|View full text |Cite
|
Sign up to set email alerts
|

Metal doped armchair graphene nanoribbons: electronic structure, carrier mobility and device properties

Abstract: Metal doping induced tuning effects on geometry, electronic structure, carrier mobility, and device properties of armchair graphene nanoribbons are studied systematically and analyzed in detail.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 51 publications
0
11
0
Order By: Relevance
“…After calculating convergence, it is found that O-BN-H and H-BN-H are non-magnetic (NM) for all these settings, and O-BN-O and H-BN-O are the NM state for all AFM settings, but both of them have a welldefined FM state. To identify the ground state for O-BN-O and H-BN-O, magnetized energy is calculated, which is defined as [41]:…”
Section: Magneto-electronic Propertymentioning
confidence: 99%
“…After calculating convergence, it is found that O-BN-H and H-BN-H are non-magnetic (NM) for all these settings, and O-BN-O and H-BN-O are the NM state for all AFM settings, but both of them have a welldefined FM state. To identify the ground state for O-BN-O and H-BN-O, magnetized energy is calculated, which is defined as [41]:…”
Section: Magneto-electronic Propertymentioning
confidence: 99%
“…Theoretical studies are important to understand the effects brought by factors such as doping and curvature in GNRs and to design GNR-based materials rationally. However, realistic GNRs typically contain more than 10,000 carbon atoms, where the distribution of dopants and the various geometric structures usually break the spatial symmetries of GNRs. , Most existing first-principles methods are suitable for small systems containing less than 1,000 atoms or periodic systems with small cells, and almost all semiempirical methods can study the direct coupling within only a few atomic layers (∼0.5 nm), , and thus many reported theoretical works are only applicable to a few dopants embedded in small periodic cells. , Recently, we developed the dopant central insertion scheme to study the influence of the long-range dopant–dopant interaction on the properties of GNRs, but this method is hardly applicable to arbitrarily deformed molecular systems since the large molecules in such calculations can only be extended from small molecules and constructed bottom-up.…”
mentioning
confidence: 99%
“…Graphene nanoribbons (GNRs) have attracted intensive attention in recent years because of their remarkable properties and tunable electronic structures as functions of sizes and edges. Moreover, doping GNRs induces a variety of novel properties for many potential applications. For instance, H or N doping can regulate the bandgap of the GNR, subsequently modulating GNR-based materials between conducting and semiconducting. Doping can also modify carrier mobility, and thus improve the performance of GNR-based devices. ,, …”
mentioning
confidence: 99%
“…Theoretical study is of great importance to understand the reported doping effects in GNR as well as to be able to rationally design GNR-based materials. , However, realistic GNRs commonly contain more than 10,000 carbon atoms embedded with distributed dopants breaking down various space symmetries, while almost all semiempirical methods can only study direct couplings among dopants within only several atomic layers (approximately 0.5 nm), and most existing first-principles methods treat small systems containing less than 1000 atoms or periodic systems with small unit cells. , Until now, many reported theoretical works have managed only a few dopants embedded in small periodic unit cells that can study only short-range dopant couplings in GNR.…”
mentioning
confidence: 99%
See 1 more Smart Citation